2020
DOI: 10.1001/jamanetworkopen.2020.3711
|View full text |Cite
|
Sign up to set email alerts
|

Association of Racial/Ethnic Segregation With Treatment Capacity for Opioid Use Disorder in Counties in the United States

Abstract: IMPORTANCE Treatment with methadone or buprenorphine is the current standard of care for opioid use disorder. Given the paucity of research identifying which patients will respond best to which medication, both medications should be accessible to all patients so that patients can determine which works best for them. However, given differences in the historical contexts of their initial implementation, access to each of these medications may vary along racial/ethnic lines. OBJECTIVE To examine the extent to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
141
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(147 citation statements)
references
References 43 publications
6
141
0
Order By: Relevance
“…Among patients who experience non-fatal overdoses, Black patients are half as likely to obtain follow-up appointments for OUD care after discharge from the emergency room ( Kilaru et al, 2020 ). In terms of access to buprenorphine compared to methadone, a recent nationwide county-level evaluation of access to methadone and buprenorphine showed that racial segregation predicts differences in access to both medications ( Goedel et al, 2020 ), and even at the regional level, neighborhood demographic makeup drives disparities in access to both medications ( Hansen et al, 2013 ). While there has been an overall uptake of buprenorphine as a treatment for OUD, a 2018 study showed that it remains primarily accessible to white people, and to people who are beneficiaries of employer-based insurance ( Roberts et al, 2018 ).…”
Section: Disparities In Access To Moudmentioning
confidence: 99%
“…Among patients who experience non-fatal overdoses, Black patients are half as likely to obtain follow-up appointments for OUD care after discharge from the emergency room ( Kilaru et al, 2020 ). In terms of access to buprenorphine compared to methadone, a recent nationwide county-level evaluation of access to methadone and buprenorphine showed that racial segregation predicts differences in access to both medications ( Goedel et al, 2020 ), and even at the regional level, neighborhood demographic makeup drives disparities in access to both medications ( Hansen et al, 2013 ). While there has been an overall uptake of buprenorphine as a treatment for OUD, a 2018 study showed that it remains primarily accessible to white people, and to people who are beneficiaries of employer-based insurance ( Roberts et al, 2018 ).…”
Section: Disparities In Access To Moudmentioning
confidence: 99%
“…Although this regulatory change has expanded access to buprenorphine treatment for OUD, 44% of counties still lack a physician with a buprenorphine waiver, and only 3% of all primary care physicians nationwide are authorized to prescribe buprenorphine for OUD [12,16]. Furthermore, substantial OUD treatment inequities exist along racial and ethnic lines, with Black patients having much lower odds of receiving buprenorphine for OUD than white patients [17][18][19]. Unlike methadone and buprenorphine, both opioid agonists, the newer extended-release naltrexone is an opioid antagonist and not a controlled substance; thus, it can be prescribed by any licensed prescriber.…”
Section: Access To Treatment For Opioid Use Disordermentioning
confidence: 99%
“…Although this regulatory change has expanded access to buprenorphine treatment for OUD, 44% of counties still lack a physician with a buprenorphine waiver, and only 3% of all primary care physicians nationwide are authorized to prescribe buprenorphine for OUD (16,20). Furthermore, substantial OUD treatment inequities exist along racial and ethnic lines, with Black patients having much lower odds of receiving buprenorphine for OUD than white patients (21)(22)(23). Unlike methadone and buprenorphine, both opioid agonists, the newer extended-release naltrexone is an opioid antagonist and not a controlled substance; thus, it can be prescribed by any licensed prescriber.…”
Section: Access To Treatment For Opioid Use Disordermentioning
confidence: 99%